The Effect of Corporate Governance, Resource And Development Intensity, Intellectual Capital And Managerial Ability On Firm Value With Political Relations As A Moderating Variable - Yuliati Galuh Nur Safitri; Nurul Hasanah Uswati Dewi (University of Merdeka Malang, 2023)
Firm value is the investor's perception of the level of success of the company which is reflected in the stock price. The higher the value of the company, the greater the prosperity that will be received by the shareholders. This study aims to see the effect of corporate governance, Resource and Development intensity, intellectual capital and managerial ability on firm value with political relations as a moderating variable in construction companies listed on the Indonesia Stock Exchange for the 2018-2021 period which were selected based on purposive sampling, the sample used in this study, namely 17 construction companies. Data were analyzed using multiple linear regression and moderated regression analysis (MRA) which were processed using SPSS version 23. The results showed that there was no significant effect between RD intensity and managerial ability on firm value, while the results of corporate governance analysis and intellectual capital also had a significant effect on firm value. The moderation test states that political relations cannot strengthen the influence between corporate governance, RD intensity, intellectual capital and managerial ability on firm value.